Managing for dummies - Nelson, Bob (Tantor Media, 2019)
The fast and easy way to learn how to manage people, projects, and teams. Being a manager can be an intimidating and challenging task. Managing involves teaching new skills to employees, helping land a new customer, accomplishing an important assignment, increasing performance, and much more. The process of management can be very challenging at times, but it can also bring you a sense of fulfillment that you never imagined possible. Managing For Dummies, 3rd Edition is perfect for all levels of managers. This clearly written, easy-to-understand guide gives you practical advice on the most important aspects of managing, such as delegating as opposed to ordering, improving employees' performances, getting your message across, understanding ethics and office policies, team building and collaboration, and much more. Managing in today's lightning-speed business world requires that you have the latest information and techniques for getting the job done. Managing For Dummies, 3rd Edition provides you with straightforward advice and up-to-the-minute strategies for dealing with anything that comes your way.